Combined multichannel intraluminal impedance and pH testing in infants and young children—a narrative review - Sequeira Gomes, Rochelle; Abraham, Sheeja; Favara, Michael T.; Sloane, Amy J.; Aghai, Zubair H. (Frontiers in Pediatrics, 2025)
Gastroesophageal reflux disease (GERD) is common in infants and young children, and thediagnosis and characterization of the disease continues to evolve in recent times. The typicalsymptoms thought to be related to GERD in young children are often nonspecific andubiquitous, underscoring the need for diagnostic testing in patients who have severe symptomsor complications related to GERD. Combined multichannel intraluminal impedance and pHtesting (MII-pH) is a diagnostic tool that can be used to study the frequency andseverity of gastroesophageal reflux. Compared to other diagnostic devices, MII-pH hasthe advantage of detecting both acidic and alkaline reflux events, as well as allows the study of thetemporal association of symptoms with GER events. Using the diagnostic parameters definedand symptom association data obtained, MII-pH can then be used to classify patients as havingGERD (with either predominantly acid or alkaline reflux), non-erosive reflux disease or NERD (when noevidence of esophagitis is noted on endoscopy), hypersensitive esophagus (positive symptom association only) and functional heartburn (normal study). The application of this disease classification to GERD in young children is relatively new and needs further validation. Even so, classifying GERD into these phenotypes using MII-pH allows for more precise and individualized therapeutic decisions. Emerging research has also suggested MII-pH testing can be used to predict changes in mucosal integrity and study the motility of the esophagus in children. Although the use of MII-pH in children with a large range of disease processes is becoming more widespread, there are important limitations to note in the interpretation of results of MII-pH in young children, due to the relative lack of normative data obtained from truly healthy children.